Mitral Valve Prolapse with Rigid Annular Calcifications: A New Technique for Mitral Valve Replacement - Wallsh, Eugene (1985)
Severe calcification of the mitral annulus presents a technical challenge in valve replacement, and in the case reported here, we replaced the valve with a new technique. Employing a rim of tissue created from the supra-annular left atrium imbricated to the edge of the posterior mitral leaflet, we created a substitute “annulus” for prosthetic valve fixation.